Metabolic and microbiota response to arginine supplementation and cyclic heat stress in broiler chickens - Brugaletta, Giorgio; Laghi, Luca; Zampiga, Marco; Oliveri, Chiara; Indio, Valentina; Piscitelli, Raffaela; Pignata, Stefano; Petracci, Massimiliano; De Cesare, Alessandra; Sirri, Federico (Frontiers in Physiology, 2023)
Little attention has been paid to the biological role of arginine and its dietary supplementation in broilers under heat stress (HS) conditions. Therefore, the main aim of this study was to assess the response of broilers to arginine supplementation and cyclic HS, with a focus on liver, pectoral muscle, and blood metabolic profiles and the cecal microbiota. Day-old male Ross 308 broilers (n = 240) were placed in 2 rooms with 12 pens each for a 44-day trial. Pens were assigned to one of two groups (6 pens/group/room): the control group (CON) was given a basal diet in mash form and the treated group (ARG) was fed CON diet supplemented with crystalline L-arginine. The total arginine:lysine ratio of CON diet ranged between 1.02 and 1.07, while that of ARG diet was 1.20. One room was constantly kept at thermoneutral (TN) conditions, while the birds in the other room were kept at TN conditions until D34 and subjected to cyclic HS from D35 onwards (~34 °C; 9:00 AM-6:00 PM). Blood, liver, Pectoralis major muscle, and cecal content were taken from 2 birds per pen (12 birds/group/room) for metabolomics and microbiota analysis. Growth performance data were also collected on a pen basis. Arginine supplementation failed to reduce the adverse effects of HS on growth performance. Supplemented birds showed increased levels of arginine and creatine in plasma, liver, and P. major and methionine in liver, and reduced levels of glutamine in plasma, liver, and P. major. HS altered bioenergetic processes (increased levels of AMP and reduced levels of fumarate, succinate, and UDP), protein metabolism (increased protein breakdown to supply the liver with amino acids for energy production), and promoted the accumulation of antioxidants and protective molecules (histidine-containing dipeptides, beta-alanine, and choline), especially in P. major. Arginine supplementation may have partially counterbalanced the effects of HS on energy homeostasis by increasing creatine levels and attenuating the increase in AMP levels, particularly in P. major. It also significantly reduced cecal observed diversity, while HS increased alpha diversity indices and affected beta diversity. Results of taxonomic analysis at the phylum and family level are also provided.